Answer: [tex]x=-\frac{3}{2}\ or\ x=2[/tex]
Step-by-step explanation:
Given the following Quadratic equation:
[tex]2x^2 - x - 6 = 0[/tex]
You can use the Quadratic formula in order to solve it.
The Quadratic formula is:
[tex]x=\frac{-b\±\sqrt{b^2-4ac} }{2a}[/tex]
In this case you can identify that:
[tex]a=2\\b=-1\\c=-6[/tex]
Therefore, knowing these values, you can substitute them into the Quadratic formula.
Then, you get:
[tex]x=\frac{-(-1)\±\sqrt{(-1)^2-4(2)(-6)} }{2)(2)}\\\\\\x=-\frac{3}{2}\ or\ x=2[/tex]